Global Governance in a World of Change - Barnett, Michael N.; Pevehouse, Jon C. W.; Raustiala, Kal (Social Sciences, 2021)
Global governance is changing, yet many disagree about how. This book introduces the idea of modes of governance, examining three different kinds - markets, hierarchies, and networks - and their evolution in contemporary world politics. This framework offers a fundamentally different way to analyse changes in global governance.